Analysis of Pedagogical Skills of Prospective PGMI Teachers in Microteaching Courses: Analisis Keterampilan Demonstrasi Pedagogik Calon Guru SD/MI dalam Mengajar IPA Pada Matakuliah Microteaching - Lestari, Ati (SEARCH: Science Education Research Journal, 2025)
Analysis of Prospective Teachers' Pedagogical Capabilities is a competency that teachers must have, especially in science learning. It is important for prospective elementary school teachers to master it, because elementary school is the beginning of students gaining knowledge and skills of scientific processes which are formed through the practice of science competencies. Having good pedagogical skills will have an impact on learning outcomes. The aim of this research is to determine and describe the pedagogical abilities of PGMI semester 6 students. The method used in this research is qualitative descriptive research, namely research that aims to understand the phenomena experienced by research subjects, for example behavior, perception, motivation to act. This research obtained results carried out by sixth semester students of PGMI. There are 7 criteria assessed based on the microteaching assessment rubric, namely mastering student characteristics with an average of 3.7 in the good category. master learning theory and educational learning principles with an average of 3.6 good. Curriculum development related to the subjects taught is in the poor category with an average of 2.7. implementation of educational learning on average was 3.03. Facilitate the development of students' potential to actualize the various potentials they have in the insufficient category with an average of 3.4 in the sufficient category. communicate effectively, empathetically and politely with students with an average of 3.1 which is in the sufficient category. carrying out the evaluation is in the good category with an average of 3.6. Based on the research results for each pedagogical criterion, it can be seen that the criteria that still need to be improved are the ability to develop curriculum, educational learning activities, communication.